Special issue on the Design and Engineering of Cryptographic Solutions for Secure Information Systems - Elci, Atilla; Pieprzyk, Josef; Orgun, Mehmet A.; Chefranov, Alexander (Wiley-Blackwell, 2012)
[Abstract Not Available]